Crime online: correlates, causes, and context - Holt, Thomas J. (Carolina Academic Press, 2021)
"In light of the increasing adoption of technology, it is critical that researchers explore the complex effects of computer technology on human behavior and the intersection of real world and virtual experiences. Crime Online uses empirical tests and unique data to provide detailed criminological explorations of multiple forms of cybercrime, including phishing, hacking, and sex crimes. This text also includes a comprehensive exploration of cyberterrorism and activism in online environments. The law enforcement and policy responses to cybercrimes at the local, state, and federal level are also discussed in detail. This work provides practical policy discussions that will benefit academics, law enforcement, legal counsel, and students at the undergraduate and graduate level"--